Bilirubin binding in jaundiced newborns: from bench to bedside?. (October 2018) - Ahlfors, Charles; Bhutani, Vinod; Wong, Ronald; Stevenson, David
Abstract Background: Bilirubin-induced neurologic dysfunction (BIND) is a spectrum of preventable neurological sequelae in jaundiced newborns. Current total plasma bilirubin (B T ) concentration thresholds for phototherapy and/or exchange transfusion poorly predict BIND. Methods: The unbound (free) bilirubin (B f ) measured at theseB T thresholds provides additional information about the risk for BIND.B f can be readily adapted to clinical use by determiningB f population parameters at currentB T thresholds. These parameters can be established using a plasma bilirubin binding panel (BBP) consisting ofB T, B f, and two empiric constants, the maximumB T (B Tmax ) and the corresponding equilibrium association bilirubin constant (K).Results: B Tmax and K provide the variables needed to accurately estimateB f atB T  < B Tmax to obtainB f at thresholdB T in patient samples. OnceB f population parameters are known, the BBP in a newborn can be used to identify poor bilirubin binding (higherB f at the thresholdB T compared with the population) and increased risk of BIND. Conclusion: The BBP can also be used in jaundice screening to better identify the actualB T at which intervention would be prudent. The BBP is used with currentB T thresholds to better identify the risk of BIND and whether and when to intervene.